Analisis Distribusi Kekayaan Dalam Prespektif Ekonomi Islam Menurut Ibn Kaldun - M, Mawardi; Mahera, Rofiqo Meili (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
According to Ibn Khaldun, a great thinker in the social and economic fields. The type of research used is qualitative research with a descriptive analytical approach. In this study, the author examines the main concepts in Ibn Khaldun's thoughts related to the distribution of wealth, such as the theory of "asbab" (cause and effect), "umran" (civilization), and "al-'amal" (work) in economics. This study also explores Ibn Khaldun's views on the role of the state, society, and factors that influence the inequality of wealth distribution in society. The results of the study indicate that Ibn Khaldun identified economic inequality as a result of social injustice and structural factors in society. In addition, Ibn Khaldun emphasized the importance of equitable distribution of wealth to achieve the welfare of society as a whole. This study contributes to understanding the concept of wealth distribution within the framework of Islamic economics, as well as its relevance in dealing with contemporary economic and social problems. This study aims to analyze the distribution of wealth from an Islamic economic perspective.